PENGARUH PELATIHAN KERJA, PENGEMBANGAN KARIR DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. DEKOR ASIA JAYAKARYA - Rahayu, Niken Wulan; Subiyanto, Didik; Kusuma, Nala Tri (Politeknik Bisnis Indonesia, 2025)
Dekor Asia Jayakarya is a manufacturing company established in 1997, producing bamboo and wood decorations and crafts. Approximately 99% of its products are exported to various countries, including garden accessories, hotel supplies, home decor, bamboo fences and furniture, and natural crafts such as mosaics and household appliances—all made from sustainable Indonesian natural resources. The main objective of this study is to determine how Job Training, Career Development, and Organizational Culture influence Employee Performance at PT. Dekor Asia Jayakarya. This type of research is quantitative descriptive research. The data collection technique uses a questionnaire. The population of this study was 50 people with a sample of 50 employees, who were selected as a whole so that saturated sampling was used. The results of this study indicate that job training does not affect employee performance, career development variables do not affect employee performance, and organizational culture has a positive effect on employee performance.